The Digitalization of Financial Markets The Socioeconomic Impact of Financial Technologies - Marszk, Adam; Lechman, Ewa (Taylor & Francis, 2022)
"The book provides deep insight into theoretical and empirical evidence on information and communication technologies (ICT) as an important factor affecting financial markets. It is focused on the impact of ICT on stock markets, bond markets, and other categories of financial markets, with the additional focus on the linked FinTech services and financial institutions. Financial markets shaped by the adoption of the new technologies are labelled 'digital financial markets'. With a wide-ranging perspective at both the local and global levels from countries at varying degrees of economic development, this book addresses an important gap in the extant literature concerning the role of ICT on the financial markets. The consequences of these processes had until now rarely been considered in a broader economic and social context, particularly when the impact of FinTech services on financial markets is taken into account. The book's theoretical discussions, empirical evidence and compilation of different views and perspectives make it a valuable and complex reference work. Information Classification: General The principal audience of the book will be scholars in the fields of finance and economics. The book also targets professionals in the financial industry who are directly or indirectly linked to the new technologies on the financial markets, in particular various types of FinTech services."